2014
DOI: 10.1155/2014/243286
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Angioma of the Corpus Callosum Presenting with Acute Psychosis

Abstract: Psychiatric symptoms may occasionally be related to anatomic alterations of brain structures. Particularly, corpus callosum lesions seem to play a role in the change of patients' behavior. We present a case of a sudden psychotic attack presumably due to a hemorrhagic cavernous angioma of the corpus callosum, which was surgically removed with complete resolution of symptoms. Although a developmental defect like agenesis or lipoma is present in the majority of these cases, a growing lesion of the corpus callosum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…In the pediatric population, symptoms associated with lipomas are nonspecific neurologic complaints such as headache, dizziness, seizures, or global psychomotor delay, which affects language and gross psychomotor skills (Chaubey et al, 2015). Many studies have reported neuropsychiatric symptoms due to lesions or developmental defects on the corpus callosum (Pavesi et al, 2014). Other clinical presentations associated with lipomas in the corpus callosum include paralysis, convulsive seizures, behavioral disturbances, intellectual disability, and cranial nerve impairment.…”
Section: Discussionmentioning
confidence: 99%
“…In the pediatric population, symptoms associated with lipomas are nonspecific neurologic complaints such as headache, dizziness, seizures, or global psychomotor delay, which affects language and gross psychomotor skills (Chaubey et al, 2015). Many studies have reported neuropsychiatric symptoms due to lesions or developmental defects on the corpus callosum (Pavesi et al, 2014). Other clinical presentations associated with lipomas in the corpus callosum include paralysis, convulsive seizures, behavioral disturbances, intellectual disability, and cranial nerve impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility to consider is psychosis secondary to mass effect or bleeding from a cavernoma. Case reports have been documented regarding psychosis secondary to cavernomas and tend to be in the setting of hemorrhagic transformations [ 19 , 20 ]. Although the MRI done upon admission showed stability in the cavernomas and no hemorrhages, the observed vascular malformations may have put her at a risk for psychotic development.…”
Section: Discussionmentioning
confidence: 99%
“…[ 9 ] Isolated cases presenting with neuropsychiatric manifestations following corpus callosum lesions have been reported by Durst and Rosca-Rebaudengo,[ 10 ] Tanaghow et al .,[ 11 ] Fersten et al .,[ 12 ] and Pavesi et al . [ 13 ] It has been proposed that corpus callosum pathologies increase the risk for psychiatric symptoms by interfering with corticocortical interhemispheric activity. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 13 ] It has been proposed that corpus callosum pathologies increase the risk for psychiatric symptoms by interfering with corticocortical interhemispheric activity. [ 13 ]…”
Section: Discussionmentioning
confidence: 99%